1997
DOI: 10.1046/j.1471-4159.1997.69062413.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullary Secretion of DOPA, Catecholamines, Catechol Metabolites, and Neuropeptides

Abstract: Catecholamines and their metabolites have been proposed as markers of sympathetic nervous system stimulation. However, the adrenal medulla is a rich source of catecholamines and catecholamine metabolites and may play a significant role in plasma levels of these compounds. In addition to adrenal catecholamine metabolite efflux, the role of the catecholamine precursor 3,4‐dihydroxyphenylalanine (DOPA) has not been fully evaluated. The simultaneous effluxes of catecholamines, metabolites, DOPA, and neuropeptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…But, the question remains: how significant is the relative abundance of immune cell-derived catecholamines in comparison to the main catecholamineproducing organ, the adrenal medulla or presynaptic neurons? The adrenomedullary baseline production of epinephrine and norepinephrine in rodents is about 730pg/mL/min and 102pg/mL/min, respectively (26). In a recent study, 10 7 rat neutrophils produced about 100pg/mL and 20pg/mL while 10 7 rat macrophages released nearly 375pg/mL of epinephrine and 50pg/mL of norepinephrine when stimulated with 50ng/mL LPS (11).…”
Section: Evidence For De Novo Synthesis Storage Release and Inactimentioning
confidence: 99%
“…But, the question remains: how significant is the relative abundance of immune cell-derived catecholamines in comparison to the main catecholamineproducing organ, the adrenal medulla or presynaptic neurons? The adrenomedullary baseline production of epinephrine and norepinephrine in rodents is about 730pg/mL/min and 102pg/mL/min, respectively (26). In a recent study, 10 7 rat neutrophils produced about 100pg/mL and 20pg/mL while 10 7 rat macrophages released nearly 375pg/mL of epinephrine and 50pg/mL of norepinephrine when stimulated with 50ng/mL LPS (11).…”
Section: Evidence For De Novo Synthesis Storage Release and Inactimentioning
confidence: 99%
“…Immunoprecipitation assay also revealed that the interaction between GPR143 and α 1B AR was enhanced by l -DOPA. Importantly, the enhancement was observed at a concentration comparable to those of plasma l -DOPA (10–20 nM) (Chritton et al, 1997; Goldstein et al, 2003; Masukawa et al, 2017). GPR143, when functionally coupled with α1 B AR, may have significantly more affinity for l -DOPA than when not forming heteromers with α1 B AR (Masukawa et al, 2017).…”
Section: Receptor Candidates Targetted By L-dopa: Their Localization mentioning
confidence: 92%
“…Although there are a large number of reports about determination of neurotransmitters in neuronal samples, however there is no method to assay all 14 compounds simultaneously in BCC samples. The secretion of dihydroxyphenylalanine, catecholamines, catecholamine metabolites and neuropeptides in adrenal chromaffin cells has been determined using HPLC with electrochemical detection . NA, AD and DA levels have also been determined using electrochemical detection, and NA, AD, DA and 5‐HT have been studied using HPLC‐MS in BCCs .…”
Section: Introductionmentioning
confidence: 99%